Genetic Influences on Behavioral Outcomes After Childhood TBI: A Novel Systems Biology-Informed Approach - Kurowski, Brad G.; Treble-Barna, Amery; Pilipenko, Valentina; Wade, Shari L.; Yeates, Keith Owen; Taylor, H. Gerry; Martin, Lisa J.; Jegga, Anil G. (Frontiers in Genetics, 2019)
Objectives: To test whether genetic associations with behavioral outcomes after early childhood traumatic brain injury (TBI) are enriched for biologic pathways underpinning neurocognitive and behavioral networks. Design: Cross-sectional evaluation of the association of genetic factors with early (~ 6 months) and long-term (~ 7 years) post-TBI behavioral outcomes. We combined systems biology and genetic association testing methodologies to identify biologic pathways associated with neurocognitive and behavior outcomes after TBI. We then evaluated whether genes/SNPs associated with these biologic pathways were more likely to demonstrate a relationship (i.e., enrichment) with short and long-term behavioral outcomes after early childhood TB compared to genes/SNPs not associated with these biologic pathways. Setting: Outpatient research setting Participants: 140 children, ages 3-6:11 years at time of injury, admitted for a moderate/severe TBI or orthopedic injuries (OI). Interventions: Not Applicable Main Outcome Measures: Child Behavior Checklist total problems T score. Results: Systems biology methodology identified neuronal systems and neurotransmitter signaling (Glutamate receptor, dopamine, serotonin, and calcium signaling), inflammatory response, cell death, immune systems, and brain development as important biologic pathways to neurocognitive and behavioral outcomes after TBI. At 6 months post injury, the group (TBI versus OI) by polymorphism interaction was significant when the aggregate signal from the highest ranked 40% of case gene associations was compared to the control set of genes. At ~ 7 years post injury, the selected polymorphisms had a significant main effect after controlling for injury type when the aggregate signal from the highest ranked 10% of the case genes were compared to the control set of genes Conclusions: Findings demonstrate the promise of applying a genomics approach, informed by systems biology, to understanding behavioral recovery after pediatric TBI. A mixture of biologic pathways and processes are associated with behavioral recovery, specifically genes associated with cell death, inflammatory response, neurotransmitter signaling, and brain development. These results provide insights into the complex biology of TBI recovery.